The Red Blood Cell—Inflammation Vicious Circle in Sickle Cell Disease - Nader, Elie; Romana, Marc; Connes, Philippe (Frontiers in Immunology, 2020)
Sickle cell disease (SCD) is a genetic disease caused by a single mutation in the -globin gene, leading to the production of an abnormal hemoglobin called hemoglobin S (HbS), which polymerizes under deoxygenation, and induces the sickling of red blood cells (RBCs). Sickled RBCs are very fragile and rigid, and patients consequently become anemic and develop frequent and recurrent vaso-occlusive crises. However, it is now evident that SCD is not only a RBC rheological disease. Accumulating evidence shows that SCD is also characterized by the presence of chronic inflammation and oxidative stress, participating in the development of chronic vasculopathy and several chronic complications. The accumulation of hemoglobin and heme in the plasma, as a consequence of enhanced intravascular hemolysis, decreases nitric oxide bioavailability and enhances the production of reactive oxygen species (ROS). Heme and hemoglobin also represent erythrocytic danger-associated molecular pattern molecules (eDAMPs), which may activate endothelial inflammation through TLR-4 signaling and promote the development of complications, such as acute chest syndrome. It is also suspected that heme may activate the innate immune complement system and stimulate neutrophils to release neutrophil extracellular traps. A large amount of microparticles (MPs) from various cellular origins (platelets, RBCs, white blood cells, endothelial cells) is also released into the plasma of SCD patients and participate in the inflammation and oxidative stress in SCD. In turn, this pro-inflammatory and oxidative stress environment further alters the RBC properties. Increased pro-inflammatory cytokine concentrations promote the activation of RBC NADPH oxidase and, thus, raise the production of intra-erythrocyte ROS. Such enhanced oxidative stress causes deleterious damage to the RBC membrane and further alters the deformability of the cells, modifying their aggregation properties. These RBC rheological alterations have been shown to be associated to specific SCD complications, such as leg ulcers, priapism and glomerulopathy. Moreover, RBCs positive for the Duffy antigen receptor for chemokines may be very sensitive to various inflammatory molecules that promote RBC dehydration and increase RBC adhesiveness to the vascular wall. In summary, SCD is characterized by a vicious circle between abnormal RBC rheology and inflammation, which modulates the clinical severity of patients.